2016
DOI: 10.3329/jbau.v12i2.28691
|View full text |Cite
|
Sign up to set email alerts
|

Yield performance of some transplant aman rice varieties as influenced by different levels of nitrogen

Abstract: The experiment was carried out during the period of June to November 2013 at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh with a view to examine the yield performance of some transplant aman rice varieties as influenced by different levels of nitrogen. The experiment consisted of four varieties viz. BRRI dhan49, BRRI dhan52, BRRI dhan56, BRRI dhan57 and four levels of N viz. 0, 46, 60 and 75 kg ha -1 . The experiment was laid out in a randomized complete block design with three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 5 publications
14
25
0
Order By: Relevance
“…The highest number of total tillers hill -1 (13.39) was recorded in BRRI dhan69 followed by BRRI dhan74 while the lowest number of total tillers hill -1 (11.35) was recorded in BRRI dhan28. Similar results were reported by Jisan et al (2014) who reported that number of total tillers varied among the varieties. The production of total tillers hill -1 differed significantly at 1% level of significance due to different date of transplanting (Table 1).…”
Section: Number Of Total Tillers Hill -1supporting
confidence: 90%
See 1 more Smart Citation
“…The highest number of total tillers hill -1 (13.39) was recorded in BRRI dhan69 followed by BRRI dhan74 while the lowest number of total tillers hill -1 (11.35) was recorded in BRRI dhan28. Similar results were reported by Jisan et al (2014) who reported that number of total tillers varied among the varieties. The production of total tillers hill -1 differed significantly at 1% level of significance due to different date of transplanting (Table 1).…”
Section: Number Of Total Tillers Hill -1supporting
confidence: 90%
“…The highest number of grains panicle -1 (130.90) was recorded in BRRI dhan69, which was statistically identical with BRRI dhan58 and the lowest number of grains panicle -1 (119.50) was recorded in BRRI dhan28, which was at par with BRRI dhan67. This trend could be explained by the varietal differences in genetic make-up (Shaha et al, 2014;Jisan et al, 2014;Sarkar et al, 2014). Date of transplanting showed significant variation in number of grains panicle -1 at 1% level of probability ( reported that early transplanting produced a greater number of grains/panicles than the late transplanting.…”
Section: Number Of Grains Panicle -1mentioning
confidence: 99%
“…On the other hand, reduction of aforesaid yield component due to application of less nitrogen (60 kg N ha -1 ) and control treatment were mainly responsible for the reduced grain yield in these treatments. The increase of grain yield of rice by nitrogen application is in agreement with the findings of many researchers (Sing and Sing, 1998;Islam et al, 2014;Jisan et al, 2014 andRay et al, 2015). The highest harvest index was obtained in control condition (0 kg N ha -1 ) which gradually decreased with the increase of N application and reached at the lowest one at 120 kg N ha -1 .…”
Section: Effect Of Number Of Seedlings Hill -1supporting
confidence: 91%
“…Nuruzzaman et al (2000) noticed that number of tillers hill -1 differed among the varieties. Varietal differences regarding grain yield was reported elsewhere (Tyeb et al 2013;Jisan et al, 2014;Pal et al, 2016). The highest harvest index (45.00%) was recorded in BRRI dhan70, which was at par with BRRI dhan71 and the lowest one in BRRI dhan72.…”
Section: Introductionmentioning
confidence: 59%